The Intersection of Religion, Public Policy, and Women's Online Activism in Sri Lanka and Afghanistan: A Comparative Analysis - Debasish Nandy; Ananta Kumar Besra (Religion and Policy Journal, 2024)
Research Problem: Women’s activism through social media in South Asia, particularly in Sri Lanka and Afghanistan, is shaped by a complex interplay of religion, public policy, and socio-political contexts. While social media offers opportunities for empowerment and advocacy, its role remains contested due to societal barriers, political constraints, and religious influences.